Pengaruh Motivasi, Ekspektasi Pendapatan, dan Persepsi Mahasiswa terhadap Minat Berwirausaha dengan Pemahaman Akuntansi sebagai Variabel Moderating - Ridhia Melliyani Noor; Saiful Anwar (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study was to describe the effect of motivation, income expectations, student perceptions of interest in entrepreneurship with accounting understanding as a moderating variable. This type of research uses quantitative methods. The population is Accounting Students of the "Veteran" East Java National Development University Class of 2018-2019. Samples were taken using simple random sampling, resulting in 226 respondents. The type of data used in this study is primary data. The analysis technique and hypothesis testing in this study used WarpPLS 7.0. The results of this study are (1) motivation has a positive and significant effect on interest in entrepreneurship, (2) income expectations have a positive and significant effect on interest in entrepreneurship, (3) student perceptions have a positive and significant effect on interest in entrepreneurship, (4) understanding of accounting is not able to moderate motivational variables on interest in entrepreneurship, (5) understanding of accounting is not able to moderate income expectations of interest in entrepreneurship, (6) understanding of accounting is able to moderate students' perceptions of interest in entrepreneurship. Keywords: motivation, income expectations, student perceptions, interest in entrepreneurship, accounting understanding